Nhận dạng đường cong tín hiệu theo cách tiếp cận xử lý ảnh một chiều - Thanh, Le Tu (Journal of Computer Science and Cybernetics, 2018)
This paper deals with the recognition of signals, which can be sampled to be received as a homomorphic image by a micro computer. The focus of the paper is a technique to recognizebasic parts of the signal curve. An  application of  from a m point group of image point on the curve to a value is introduced to discover the relationship between this group and  the varying  of the amplitude. The technical characteristics are considered to  support the use of  the technique. At last, a concret application f, which is composed between two applications f1 and f2, is discursed as an illustrating example for the  technique.